The Species of enteromorpha from redcliffe, Southern Queensland = Jenis-jenis enteromorpha dari redcliffe, Queensland Selatan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
ABSTRACT: Nine species and one subspecies of Enteromorpha from Redcliffe have been recorded, and identified as Enteromorpha ralfsii, E. intestinalis, E. compressa, E. clathrata, Enteromorpha sp., E. ahlneriana, E. prolifera, E. flexuosa and E. flexuosa subsp. linziformis. The last five species and one subspecies mentioned above have not been recorded before. Identification has been based on morphological and anatomical characters.